HUBUNGAN ANTARA PERILAKU KELUARGA TERHADAP KEJADIAN DEMAM BERDARAH DENGUE DI KELURAHAN PANCORAN MAS - Jihaan, Sarah; Chairani, Aulia; Mashoedojo, Mashoedojo (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2017)
Dengue Hemorrhagic Fever was a viral endemic disease which has became on of common health problems encountered in Indonesian. The incidence rate of DHF in Kelurahan Pancoran Mas had been become the highest and significant increase from 2010-2015. This research determine the correlation between family health behavior and the incidens of DHF. This is an analytic survey research by cluster random sampling. The subject were all of the people who live in Kelurahan Pancoran Mas with produced a sample is 136 respondents. Data collection use the questioner and analyse by chi square statistic test (P=0,05). From the research result was found that there’s no correlation of family health behavior with dengue incidence with P=0,254 (P>0,05). It can be concluded that the alternative hypothesis in this study (Ha) rejected and the hypothesis (Ho) is accepted where there’s no correlation between of family health behavior with dengue incidence.